The mitochondrial genome of the assassin bug Sclomina erinacea (Hemiptera: Reduviidae) - Qian Zhao; Ping Zhao; Hu Li; Wanzhi Cai; Fan Song (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome (mitogenome) of the assassin bug, Sclomina erinacea Stål, was determined in the present study. The sequenced mitogenome is a typical circular DNA molecule which is 15,828 bp in length, containing 13 protein-coding genes, two rRNA genes, 22 tRNA genes and a putative control region. All protein-coding genes are initiated by ATN codons and terminated by TAA or TAG codons except COII, COIII and ND4 which use a single T residue as the stop codon. All tRNAs have the cloverleaf structure with the exception of tRNASer(AGN) and the length of them range from 62 to 70 bp. The control region is 818 bp long with an A + T content of 67.1%. The phylogenetic analysis supports the monophyly of Harpactorinae and Sclomina erinacea is the closest relative to Macracanthopsis nodipes.